Facing migration under adverse conditions: challenges and resilience in the Colombo-Venezuelan border area - Gloria Omaira Bautista; Axel Kroeger; Nelly Rosero Castillo; Eduardo Gabriel Osorio Sanchez; Dianne Sofía Gonzales Escobar; Rafael Olarte; Sonia Diaz Monsalve (BMC Public Health)
Abstract Background Internal displacement and cross-country migration are an increasing global phenomenon drawing the attention of politicians and the public. Causes and effects on the migrants and receptor populations are varied and often shaped by immigration laws and how migrants and refugees are being dealt with by local conditions, policy frameworks and by the host population (receptors). The massive influx of Venezuelan migrants into Colombia for more than a decade has characteristics which warrant a systematic analysis to identify contextual and individual factors favouring and hindering the well-being of migrants and their new Colombian neighbours of the receptor population. Methods A household interview survey was conducted in two cities of the Colombo-Venezuelan border: Cucuta and Valledupar. The survey included 412 migrant families, comprising 1656 individuals, and 317 Colombian neighbour families, totalling 1077 individuals. Only migrants staying in the border area for more than 6 months and excluding “short term migrants” who cross the border only for getting treatment or schooling for their children. We used systematic sampling in neighbourhoods with the highest concentration of migrants. The sampling interval was set at every 7 and 6 migrant households. Ethical approval was obtained by the ethics committees of the three participating universities and the local health authority. Results Venezuelan migrants were younger than their Colombian neighbours (22.04 and 28.69 years respectively). The primary reason for migration among these individuals was economic (84.1%) and much less for political reasons (< 10%); about half of them had entered the country through an irregular crossings, known locally as “trochas”. Within this group, around 28% reported experiencing various forms of violence, particularly physical or verbal aggression, much less sexual assault. Following their arrival, irregular migrants had to go through a regulation (legalization) process in Colombia, with 48.1% having either initiated or completed this process. The target migrants have been living in Colombia for an average of 4.3 years, mostly in poor shelters, just as their Colombian neighbours (64.8% and 53% respectively). Both groups, but particularly the migrants, belonged to the lower socioeconomic strata according to their educational levels and occupations (street vendors including street musicians and entertainers; 21.6% of migrants and 10.6% of Colombian neighbours). They all had stressful life events recently, with economic hardship being the most significant one, especially among migrants. In terms of exposure to physical violence, the rates were almost equal for both groups. However, specific incidents such as theft, assault and intended homicide were more often experienced by the Colombian receptor population. Legal services were often sought by migrants, mostly in a special advice centre for migrants or from international organizations while their Colombian neighbours resorted mainly to national institutions including the police. For health issues migrants had often to go to private services with out-of-pocket payment while the Colombians accessed the health system through the subsidized or pre-paid health insurance. Emotional and psychological symptoms were frequent in both groups but more among migrants. The Colombian respondents had more frequently negative comments about migrants but acknowledged that they were exploited in Colombia and that they contribute to community activities and the local economy. Conclusion Both Venezuelan migrants and their Colombian neighbours suffer significantly from the consequences of poverty and stressful living conditions. As such, they require equal attention from policymakers and public services. This attention should encompass enhanced security in the public spaces, accessible legal advice, and comprehensive health support.